The role and efficacy of generic learning and study support: what is the experience and perspective of academic staff? - Richard Bailey (Association for Learning Development in Higher Education (ALDinHE), 2010)
The importance of student learning and study support is now widely recognised in higher education but empirical research into this aspect of teaching and learning is still limited in scope. In particular the experience, perceptions and understandings of academic staff constitutes a perspective which seems under-explored. This paper presents the findings of a qualitative study in this area undertaken in one institutional context. Data are presented which illustrate academic staff attitudes to, and beliefs about learning and study support and the effects of institutional practices and priorities on how this type of provision is framed and delivered. The findings have implications for the challenge of learning development in higher education.